2010
DOI: 10.1088/0004-637x/713/1/269
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Collapse and Accretion in Turbulent Gas Clouds: Implementation and Comparison of Sink Particles in Amr and SPH

Abstract: Star formation is such a complex process that accurate numerical tools are needed to quantitatively examine the mass distribution and accretion of fragments in collapsing, turbulent, magnetized gas clouds. To enable a numerical treatment of this regime, we implemented sink particles in the adaptive mesh refinement (amr) hydrodynamics code flash. Sink particles are created in regions of local gravitational collapse, and their trajectories and accretion can be followed over many dynamical times. We perform a ser… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
504
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 413 publications
(520 citation statements)
references
References 93 publications
15
504
1
Order By: Relevance
“…We make use of the sink particle routine (Federrath et al 2010) to model the formation of protostars. The results of the simulations were first presented in Seifried et al (2012Seifried et al ( , 2013.…”
Section: Initial Conditions and Basic Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We make use of the sink particle routine (Federrath et al 2010) to model the formation of protostars. The results of the simulations were first presented in Seifried et al (2012Seifried et al ( , 2013.…”
Section: Initial Conditions and Basic Resultsmentioning
confidence: 99%
“…We introduce sink particles above a density threshold of ρcrit = 1.14·10 −10 g cm −3 using an accretion radius of 3.14 AU (see Federrath et al 2010, for details). Here we only point out that the angular momentum carried by the gas will be transferred to the spin of the sink particle.…”
Section: Initial Conditions and Basic Resultsmentioning
confidence: 99%
“…The general criteria used to create sink particles include assuming a density threshold, requiring the highest level of refinement, having converging flow, or considering the local minimum of gravitational potential and/or a gravitationally bound region. In the literature, various combinations of these approaches are used and a detailed comparison of these methods was made by Federrath et al (2010). They found that a simple density threshold criterion to create sink particles is insufficient in the regime of supersonic turbulence because of local density enhancements.…”
Section: Sink Particlesmentioning
confidence: 99%
“…Sink velocities are computed based on momentum conservation. The works of Federrath et al (2010) and Bleuler & Teyssier (2014) suggest that this method of sink creation may create more sink particles. However, this may happen only in the regime where efficient fragmentation is expected, in the presence of supersonic turbulence or efficient cooling.…”
Section: Sink Particlesmentioning
confidence: 99%
“…Numerical simulations show that molecular clouds fragment down to their thermal or magnetic Jeans masses (Bonnell et al 1991;Klessen et al 1998;Klessen 2001;Bate et al 2003;Jappsen et al 2005;Federrath et al 2010). As massive stars form in stellar clusters where the mean stellar mass is of order 0.5M , the fragmentation mass must be of that order.…”
Section: Competitive Accretionmentioning
confidence: 99%